Experience Based Learning in Tanoda Program – But How? - Bencéné Fekete, Andrea (Autonomy and Responsibility Journal of Educational Sciences, 2022)
During my research I carried out interviews with students in lower grades of primary school in order to fi nd out what they mean by learning and the reasons behind their dislike concerning. During my study I introduce a mentor program („Tanoda” program), which provides an opportunity for children with disadvantaged background to learn how to learn and transforms the acquisition of knowledge pleasure for them. They acquire learning methods via playing, and other, inquiry based activities. The aim of this program is to help children with disadvantaged background in achieving success in their school environment and improve their personal comptences as well. These weekly held sessions are not coaching lessons, but personal development sessions matching to one’s specifi c needs. Besides the personal development these lessons provide opportunities to discover and support learners who need more help and who perform outstandingly.